Investigation of methodological preferences of educational researchers in Iran - Mahmood Mehrmohammadi (فصلنامه نوآوری‌های آموزشی, 2007)
The current article whose goal is reaching a clear picture of the viewpoints by the methodology instructors in the field of education and psychology in Iran is consisted of five parts First, the focus has been on the development record of methodology and the influential elements on it. The author then clarifies the researchwise theoretical framework. The current article is the product of this research. This topic begins with a critical observation about segregating methodologies into quantitative and qualitative and follows it with seventeen-fold statements that indicate the distinctions among different methodologies and makes up the base for compiling the research tools. At the end, the authors segregation stand about the distinction between methodology of biological sciences and human sciences methodology has been described. In the next part, the research methodology and the information analysis method, which is the known content analysis and purports interference is described. In this research, the cases were selected from the two groups of researchers in the field of educational sciences and psychology as samples, who represent the two different generations of researchers (preceding and recent). This tact has made possible the ground for comparing the methodology beliefs of these two groups in the information analysis field. The result of this comparison shows crave toward achieving this promising result that as time passes, not only among the recent generation but also within the preceding generation methodological multiplicity has been justified. In the status of belief and opinion, the researchers of the field of education and psychology, especially the recent group consider the methodological monopoly which underlies the legitimacy of the unique scientific method of quantitative research finished. This matter has been thoroughly discussed at the last section of the article with integrating approach, comparison, discussion, and conclusion.